Scale Transitions in Magnetisation Dynamics (Communications in Computational Physics, 2018)
Multiscale modelling is a powerful technique, which allows for computationalefficiency while retaining small-scale details when they are essential for understandinga finer behaviour of the studied system. In the case of materials modelling,one of the effective multiscaling concepts is domain partitioning, which impliesthe existence of an explicit interface between various material descriptions, forinstance, atomistic and continuum regions. When dynamic material behaviour is considered,the major problem for this technique is dealing with reflections of high frequencywaves from the interface separating two scales. In this article, a new methodis suggested, which overcomes this problem for the case of magnetisation dynamics.The introduction of a damping band at the interface between scales, which absorbshigh frequency waves, is suggested. The idea is verified by using a number of one-dimensionalexamples with fine/coarse scale discretisation of a continuum problemof spin wave propagation. This work is the first step towards establishing a reliableatomistic/continuum multiscale transition for the description of the evolution of magneticproperties of ferromagnets.